Autocracy for the people: modes of response-able action and the management of demise in Frostpunk - Dolkemeyer, Lars (Gamevironments, 2020)
In the post-apocalyptic construction simulation Frostpunk (2018) two modes of action are confronted with each other. On the one hand, the player-leaders’ decisions concern their people. The players are, in Donna Haraway’s terms, response-able for and to the survivors of a global climate collapse in a situation of co-presently “living-with and dying-with each other” (Haraway 2016, 2). The complex interdependence of social conditions and player choices in Frostpunk thus problematises any notion of winning. What is at stake is the possibility of forming a community itself by acting precisely as that community, experienced through simultaneously sharing and leading it. The second mode of action lies in the decisions that oppose the perceived well-being of the community: The players are forced to manage an inevitable demise by constructing buildings, saving resources, and advancing technologies in view of the next drop in temperatures or the next storm that will deplete all depots and diminish hope. Departing from the modes of similar dictatorship simulations, Frostpunk reconfigures the genre’s autocratic gameplay (Dor 2018, Wiemer 2008, 2012) to open new political perspectives.